Responding to the mental health needs of children in a public health service in Brazil - Marta Bartira Meirelles-Santos; Joel Giglio Sales (Universidade Estadual Paulista, Faculdade de Ciências e Letras de Araraquara, 2023)
The COVID-19 pandemic has further intensified the substantial demand for psychological treatment for children. However, in Brazil and various other nations, there is a lack of resources and evidence-based treatments focused on child mental health. Given this scenario, an evaluation of the efficacy of a pilot psychosocial group approach called "Operative Play Group" (OPG) was conducted within a public health service. This model aims not only to promote mental health but also to enhance equity through recognizing the social determinants of health. To measure behavioral problems, an analysis grounded in the principle of Intent-to-Treat was employed. However, this analysis did not demonstrate the effectiveness of the intervention. Nevertheless, through comprehensive research of cases, it was found that the program positively impacted the internalizing issues observed in children. The OPG model presents a distinctive feature as it stands out as one of the few methods incorporating dance. Dance can foster the expression of emotions and expand bodily perception. The findings of this study suggest the feasibility and relevance of utilizing body movement and dance as practical components in psychosocial interventions.